They are even larger! More (on) puzzling labor market volatilities - Hermann Gartner; Christian Merkl; Thomas Rothe (Kiel Institute for the World Economy (IfW), 2009)
This paper shows that the German labor market is more volatile than the US labor market. Specifically, the volatility of the cyclical component of several labor market variables (e.g., the job-finding rate, labor market tightness, and job vacancies) divided by the volatility of labor productivity is roughly twice as large as in the United States. We derive and simulate a simple dynamic labor market model with heterogeneous worker productivity. This model is able to explain the higher German labor market volatilities by a longer expected job duration.
Keywords: J6; E24; E32; 330; Labor Market Volatilities; Unemployment; Worker Flows; Vacancies; Job-Finding Rate; Market Tightness; Arbeitsmarkt; Arbeitsmobilität; Volatilität; Offene Stellen; Arbeitsuche; Betriebszugehörigkeit; Theorie; Deutschland